2005
DOI: 10.1158/0008-5472.can-05-0917
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Akt and eIF4E Survival Pathways by Rapamycin-Mediated Mammalian Target of Rapamycin Inhibition

Abstract: The mammalian target of rapamycin (mTOR) has emerged as an important cancer therapeutic target. Rapamycin and its derivatives that specifically inhibit mTOR are now being actively evaluated in clinical trials. Recently, the inhibition of mTOR has been shown to reverse Akt-dependent prostate intraepithelial neoplasia. However, many cancer cells are resistant to rapamycin and its derivatives. The mechanism of this resistance remains a subject of major therapeutic significance. Here we report that the inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

92
610
2
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 735 publications
(710 citation statements)
references
References 31 publications
92
610
2
6
Order By: Relevance
“…In H460, H596, H1299, H1650, SKMES-1 characterized by maintaining S6K phosphorylation after gefitinib treatment, everolimus inhibited phosphorylation of S6K and slowed proliferation, albeit to different extents especially at the lower doses. This result is in agreement with that reported by Sun et al on H460 and H1299 cell lines treated with rapamycin [39]. The high basal level of p-AKT observed in H1650 and SKMES-1 may be associated with the higher sensitivity to everolimus as reported in ovarian cancer cells [40] and in breast cancer cells [41].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In H460, H596, H1299, H1650, SKMES-1 characterized by maintaining S6K phosphorylation after gefitinib treatment, everolimus inhibited phosphorylation of S6K and slowed proliferation, albeit to different extents especially at the lower doses. This result is in agreement with that reported by Sun et al on H460 and H1299 cell lines treated with rapamycin [39]. The high basal level of p-AKT observed in H1650 and SKMES-1 may be associated with the higher sensitivity to everolimus as reported in ovarian cancer cells [40] and in breast cancer cells [41].…”
supporting
confidence: 93%
“…It is recognized that mTOR inhibition induces insulin receptor substrate-1 expression and inhibits a normally negative feedback loop resulting in AKT activation in some cancer cell lines [39,42].…”
mentioning
confidence: 99%
“…This discovery provided solid evidence that rapamycin does not completely inhibit mTOR function. In addition, a recent investigation showed that the inhibition of mTOR by rapamycin triggered the activation of survival signaling pathways, including the Akt pathway, and that this activation may contribute to drug resistance (Sun et al, 2005). This phenomenon provides support for the idea that mTOR has a positive role in regulating Akt phosphorylation that is not shared with raptor but possibly is shared with rictor (Guertin and Sabatini, 2005).…”
Section: Discussionmentioning
confidence: 84%
“…Inhibition of TOR relieves a negative feedback loop that targets IRS-1 and leads to elevated phosphorylation of Akt. Removal of this negative feedback may underlie the poor clinical responses of cancer patients treated with rapamycin (Haruta et al, 2000;Sun et al, 2005;O'Reilly et al, 2006). Combined inhibition of PI3K and TOR is more effective in reducing cancer cell growth than inhibition of either target alone (Sun et al, 2005;Fan and Weiss, 2006;.…”
Section: Oncogenic Signaling Of Class I Pi3k Isoforms a Denley Et Almentioning
confidence: 99%